FACTEURS ASSOCIÉS AUX LÉSIONS PRÉCANCÉREUSES ET CANCÉREUSES DU COL DE L’UTÉRUS DANS LA VILLE DE PARAKOU AU BÉNIN - Kabibou, Salifou; Luc, Brun; L. F. J, Akpona; Achille, Obossou A. A.; René-Xavier, Perrin (European Scientific Journal, ESJ, 2015)
Objective: To investigate the factors associated with precancerous and cancerous cervical lesions in Parakou in Benin. Materials and Methods: This study was a cross-sectional descriptive and analytical of data carried from 1 January 2012 to 31 August 2012. Visual inspection after application of acetic acid / Lugol (IVA / IVL) and biopsies were used as a screening tool in three health centers in Parakou. RESULTS: For 1057 women surveyed in this city, the incidence of cervix precancerous lesions was 6.81% and that cervix cancerous lesions was 1.04%. The average age of women surveyed was 32.62 ± 9 years. They lived as a couple in over 80% of cases. They were multiparous in 45% of cases with an age at first intercourse of 17.54 ± 2.45 years. Age, level of education, gravidity and parity had a significant relationship with the occurrence of precancerous and cancerous lesions of the cervix.